2019
DOI: 10.1177/0030222819890974
|View full text |Cite
|
Sign up to set email alerts
|

Attributions About Bereaved Spouses: Testing the Myths of Coping With Loss

Abstract: Social expectations influence how we cope with loss and how people in our social networks respond to us. Wortman and Silver outlined Western cultural assumptions, or myths, about mourning, thought to influence judgments of one’s grief response. In particular, the two myths hypothesized to affect social judgments about grievers’ adjustment were related to (a) the intensities of the grief response and (b) the duration of the grief response. We assessed if these myths affected the attributions of potential suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…The sample composition may be due to the overrepresentation of female participants in bereavement research in general [ 52 ], the use of convenience sampling, and some of our various recruitment strategies (e.g., contacting university mailing lists). However, the high degree of consistency between our main findings on PGD and stigma with the results from prior studies in community samples from different countries [ 21 23 ], also suggests that our findings generalize to different populations. To explore if the various recruitment strategies attract participants with different characteristics, future research could assess by which channel each respondent was recruited.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The sample composition may be due to the overrepresentation of female participants in bereavement research in general [ 52 ], the use of convenience sampling, and some of our various recruitment strategies (e.g., contacting university mailing lists). However, the high degree of consistency between our main findings on PGD and stigma with the results from prior studies in community samples from different countries [ 21 23 ], also suggests that our findings generalize to different populations. To explore if the various recruitment strategies attract participants with different characteristics, future research could assess by which channel each respondent was recruited.…”
Section: Discussionsupporting
confidence: 85%
“…more perceived stigma). Relatedly, Kahler et al [21] found that higher grief severity in a vignette (no diagnosis mentioned) was associated with greater reported social discomfort towards the bereaved person described in the vignette (i.e., more public stigma).…”
Section: Introductionmentioning
confidence: 99%
“…First, the present convenience sample was not representative of the general Australian population, being relatively young, mostly female, and highly educated, which may threaten generalizability of the findings. However, it should be here that prior experiments, conducted in different cultures, with different distributions of age, sex, and education levels, yielded highly similar main results (Eisma, 2018;Eisma et al, 2019;Gonschor et al, 2020;Kahler et al, 2021). Future researchers could aim to recruit representative samples to replicate and extend current findings.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 80%
“…Notably, PGD criteria differed somewhat between studies, with only the two most recent studies using current PGD ICD-11 criteria, yet the effects were generally strong and consistent. A related study demonstrated that higher grief severity in a vignette (no PGD diagnosis mentioned) related to greater reported social discomfort toward the bereaved person described in a vignette in an American sample (Kahler et al, 2021). Together, these studies illustrate that people with severe grief perceive negative social reactions (Johnson et al, 2009), which may result from public stigmatization of their grief reactions (Eisma, 2018, Eisma et al, 2019, Gonschor et al, 2020; Kahler et al, 2021).…”
mentioning
confidence: 99%